n Kwalitatiewe en kwantitatiewe perspektief op die informele sektor - Kirsten, M. A.(Maria Albertina) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.A.) -- Universiteit van Stellenbosch, 1988.